Status besi, seng dan vitamin A pada kehamilan - Hertanto Wahyu Subagio (Berita Kedokteran Masyarakat (BKM), 2005)
Introduction: Micronutrients problems in pregnancy gain less attention than iron deficiency. This study was aimed to describe iron, zinc and vitamin A status and their changes during second and third trimester of pregnancy. Methods: Serum transferrin receptor (sTfR) as measurement for iron status, zinc level and retinol were obtained from serum of 70 pregnant women who were purposively chosen. The measurements were conducted in the second and third trimester. The changes of micronutrients level were analyzed using paired t-test Results: The prevalence of anemia in the second and third trimester was 77,1% and 64,3% respectively. Only 31,4% of subjects had iron deficiency, while zinc and vitamin A deficiency occurred in 64,7% and 11,4% of the subjects respectively. The level of the micronutrients significantly changed during the third semester of pregnancy. The prevalence of iron deficiency in the third trimester decreased to 17,1%. All subjects had zinc deficiency while vitamin A deficiency was observed in 25,7% of the pregnant women Conclusion: The prevalence of zinc and vitamin A deficiency is high, as well as iron deficiency. There is an increase in iron status from second to third trimester of pregnancy. Conversely, zinc and vitamin A status decrease significantly. Keywords: anemia micronutrient pregnancy